Eradication of poverty South Asia's call for joint responsibilities. (Humanist Institute for Co-operation with Developing Countries, Netherlands, India Regional Office, 2000)
Proceedings of Eurostep South Asia Partner Consultation on Poverty Eradication and Quality of Aid in South Asia, held at Manesar, September 26-29, 2000.